2022
DOI: 10.1111/1755-6724.15026
|View full text |Cite
|
Sign up to set email alerts
|

The Formation of the Jiaodong Gold Province

Abstract: Gold deposits in Jiaodong, termed Jiaodong‐type, are tectonically located in the southeastern margin of the North China Craton. Their major features are reviewed in this paper to highlight the differences between Jiaodong deposits and other genetic types of gold deposits. The mineralization was synchronized with asthenosphere upwelling indicated by syn‐ore OIB‐like mafic dike and large‐scale crustal thinning suggested by decrease of Sr/Y from pre‐ore to syn‐ore granites. Asthenosphere upwelling induced by the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(5 citation statements)
references
References 174 publications
1
1
0
Order By: Relevance
“…( 2 [59,60], the fact that late Archean to early Proterozoic regional metamorphism identified in the study area [61][62][63] significantly predates the formation of the Xiejiagou gold deposit and the lack of early Cretaceous metamorphism strongly precludes the involvement of metamorphic fluid. This conclusion is consistent with previous studies that the Precambrian metamorphism has no genetic role to play in the formation of the Mesozoic gold mineralization in the Jiaodong area [64,65]. (4) As shown in the Ni-Co and Sb/Bi-As/Ag diagram, most pyrite samples of the Xiejiagou gold deposit fall between magmatic-related and hydrothermal-related pyrites (Figure 13a) or magmatic-related pyrite (Figure 13b), rather than metamorphic hydrothermal-related pyrite [66][67][68].…”
Section: Origin and Evolution Of Ore-forming Fluidssupporting
confidence: 93%
“…( 2 [59,60], the fact that late Archean to early Proterozoic regional metamorphism identified in the study area [61][62][63] significantly predates the formation of the Xiejiagou gold deposit and the lack of early Cretaceous metamorphism strongly precludes the involvement of metamorphic fluid. This conclusion is consistent with previous studies that the Precambrian metamorphism has no genetic role to play in the formation of the Mesozoic gold mineralization in the Jiaodong area [64,65]. (4) As shown in the Ni-Co and Sb/Bi-As/Ag diagram, most pyrite samples of the Xiejiagou gold deposit fall between magmatic-related and hydrothermal-related pyrites (Figure 13a) or magmatic-related pyrite (Figure 13b), rather than metamorphic hydrothermal-related pyrite [66][67][68].…”
Section: Origin and Evolution Of Ore-forming Fluidssupporting
confidence: 93%
“…The 193 nm ArF excimer laser, homogenized through an advanced beam delivery system, was precisely focused on the mineral surface, delivering a fluence of 10-12 J/cm 2 . Measured masses included 23 Na, 24 Mg, 27 Al, 29 Si, 31 P, 39 K, 44 Ca, 49 Ti, 55 Mn, 57 Fe, 7 Li, 9 Be, 11 B, 45 Sc, 51 V, 52 Cr, 59 Co, 60 Ni, 63 Cu, 66 Zn, 71 Ga, 73 Ge, 75 As, 85 Rb, 88 Sr, 89 Y, 91 Zr, 93 Nb, 95 Mo, 111 Cd, 118 Sn, 133 Cs, 137 Ba, 139 La, 140 Ce, 141 Pr, 146 Nd, 147 Sm, 153 Eu, 157 Gd, 159 Tb, 163 Dy, 165 Ho, 166 Er, 169 Tm, 172 Yb, 175 Lu, 178 Hf, 181 Ta, 182 W, 209 Bi, 208 Pb, 232 Th, and 238 U. Each acquisition process began with a 20 s background measurement to establish a baseline (gas blank), followed by a 60 s ablation period where a 30 µm spot diameter was used at a repetition rate of 6 Hz.…”
Section: Analytical Techniquesmentioning
confidence: 99%
“…The study of fluid-rock reaction processes is crucial for revealing element migration patterns during hydrothermal alteration, analyzing the mechanisms of hydrothermal alteration, and exploring the evolution of hydrothermal fluids, the activation, migration, and precipitation mechanisms of ore-forming elements [2]. Despite previous studies on the hydrothermal alteration of gold deposits in Jiaodong, which primarily focused on the major and trace element composition of different altered rocks to reveal the patterns of element migration between various alteration zones [2][3][4][5][6][7], it has been found that the hydrothermal alteration in Jiaodong gold deposits exhibits multi-stage superposition characteristics with complex mineral microstructures. However, the use of bulk mineral analysis to obtain results such as major and trace elements, isotopes are average values for different stages, which may differ from their actual geological significance, cannot accurately constrain the hydrothermal alteration process or mineralization process [8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…The rare earth elements, fluid inclusions and carbon and oxygen isotopes have been widely used to characterize and trace the source and evolution of hydrothermal fluids (e.g., Ohmoto and Rye, 1979;Hoefs, 1987;Bau and Dulski, 1995;Demé ny and Haranqi, 1996;Suchy et al, 2000;Deng et al, 2009;Ren et al, 2015;Du et al, 2017;Pei et al, 2017;Perry and Gysi, 2018;Quandt et al, 2018;Zhang et al, 2020;Deng et al, 2022;Wang et al, 2022). Hydrothermal calcite is predominant in veins from the Balingshan area of the Jiangling Basin, and is regarded as the optimal mineral for the examination of fluid activity.…”
Section: Introductionmentioning
confidence: 99%